The multi-scalar organization of aging-related services in US rural places. (May 2019) - Brown, David L.; Glasgow, Nina; Kulcsar, Laszlo J.; Sanders, Scott; Thiede, Brian C.
Abstract: Many rural communities in the United States are experiencing significant population aging, and these changes in age structure are often associated with shifts in economic activity. The demands for certain goods and services are expected to vary across age groups, and public- and private-sector service providers may make decisions based on their interpretation of demographic trends. The extent to which these perceived changes in the demand for services align with their provision has significant implications for the well-being of the older residents of aging communities. In this article, we draw on case studies of four aging communities across the rural United States to examine the provision of, and access to, aging-related services. We analyze how service provision is organized both within and between communities, how this organization is associated with the kinds of services available, the ways that older residents gain access to services, and the set of barriers to access they face. Our research suggests that aging-related service provision in rural communities is facilitated by partnerships among local community institutions and between them and external organizations. While in many cases population aging is associated with economic decline, the impact of demographic change is not mechanistic nor automatic. Our research shows that aging rural communities can be resilient, and that cooperative, multi-scalar relationships are a key to maintaining quality of life among older residents of communities with aging populations. Highlights: Service provision in aging communities is facilitated by partnerships between local and external organizations. Links across domains within the same community are also valuable. Aging rural communities can be resilient if cooperative, multi-scalar relationships are developed.